Effects of body condition score and parity on oxidative stress indicators of periparturient Iranian dairy buffaloes - Afshar-Hamidi, Bahram; Maheri-Sis, Naser; Sadegipanah, Abolhasan; Asri-Rezaei, Siamak; Gorbani, Abolfazl (Indian Journal of Dairy Science, 2019)
This experiment was carried out to investigate the effects of parity and body condition score (BCS) pre calving on oxidative stress indices of 43 milking buffaloes in transition period. The experiment was performed based on completely randomized design with unequal replications, using 3*4 factorial experiments comprising four levels of BCS (2.5-2.99; 3-3.49; 3.5-3.99 and 4-4.5) at two weeks before calving and three groups of parity number (1; 2-5 and >5). Blood samples were collected from experimental animals in three stages including: 14 days before parturition, parturition day and 14 days after parturition. The results showed that the serum aspartate transaminase (AST) and alkaline phosphatise (ALP) activities in the highest BCS (4-4.5) group were significantly higher than that of other BCS groups; while the serum gamma-glutamyl transaminase (GGT) activity was decreased with increasing BCS. Also blood glutathione peroxidase (GPx) activity and serum malondialdehyde (MDA) content in the lowest level of BCS (2.5-3) were significantly lower than that of other groups. The higher serum catalase activity as well as total antioxidant capacity (TAC) was observed in the BCS of 3.5-3.99. At periparturient period, MDA level and GPx and catalase activities at calving day and alanine aminotransferase (ALT) and AST at 14 days after calving were increased significantly. Moreover, it is observed that multiparous buffaloes have significantly higher oxidative stress indicators than primiparous animals. Based on the results of this study, activity of oxidative stress factors in dairy buffaloes with a higher BSC at parturition significantly increased in 14 days after calving, which indicates an increase in the metabolism of lipids and proteins in these conditions.